The Role Of Corporate Governance Characteristics In Improving The Liquidity And Profitability Of Banks During The Reconstruction Phase. (An applied study in private banks in Lattakia Governorate) - Nassour, Rim M. (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study aimed to demonstrate the role of corporate governance characteristics in improving the liquidity and profitability of banks during the reconstruction phase, by conducting an applied study in Syrian private banks, by assessing the reality of each of the disclosure, transparency, accountability, work discipline and validity, the researcher relied on the deductive approach as an approach In thinking, the descriptive approach has a procedural approach to determine the availability of corporate governance characteristics in private banks. Where the researcher distributed a questionnaire to 149 workers, the study concluded that the lowest mean average for the responses of the sample members to the phrases that measure the delegated participation of decision-making workers is 2.95, and it is less than the mean of neutrality 3, and it is significant, meaning that the bank does not have the good ability to fulfill its liabilities Traded according to the answers of the sample members. At the lowest levels, this affects the bank’s business mechanism, which is reflected in its liquidity. Then some proposals were presented, the most important of which was the necessity for the bank to work on disclosure and transparency, and to commit to disclosing the structure and policies of governance and the extent of their application. هدفت الدِّراسة إلى بيان دور خصائص حوكمة الشركات في تحسين سيولة وربحية المصارف خلال مرحلة إعادة الإعمار من خلال إجراء دراسة تطبيقية في المصارف الخاصة في محافظة اللاذقية- مصرف سورية والمهجر نموذجاً، وذلك من خلال تقييم واقع كل من الإفصاح والشفافية، والمساءلة، الانضباط بالعمل والصلاحية. اعتمدت الباحثة على المقاربة الاستنباطية كمنهج في التفكير، وعلى المنهج الوصفي كمنهج إجرائي للوقوف على مدى توافر خصائص حوكمة الشركات في المصارف الخاصة المدروسة. قامت الباحثة بتوزيع استبانة على 149 عامل، وقد خلصت الدِّراسة إلى أن أقل متوسط حسابي لإجابات أفراد العينة على العبارات التي تقيس تفويض مشاركة العاملين اتخاذ القرار هو 2.95، وهو أقل من متوسّط الحياد 3، ومعنوي، أي أنّ المصرف لا يتميز بالقدرة الجيدة للوفاء بمطلوباته المتداولة وفق إجابات أفراد العينة في أقل المستويات، وهذا يؤثر على آلية عمل المصرف الأمر الذي ينعكس على سيولته. وقدمت الباحثة بعض المقترحات كان أهمها ضرورة أن يعمل المصرف على الإفصاح والشفافية، وأن يلتزم بالإفصاح عن هيكل وسياسات الحوكمة ومدى تطبيقها.